Forage Fact Sheet Moringa - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
Brief explanation of the Moringa: plant description, forage management, cultivation, cutting, transplanting, fertilization and use